2007
DOI: 10.1152/ajpheart.00617.2006
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent peripheral tissue ischemia during coronary ischemia reduces myocardial infarction through a KATP-dependent mechanism: first demonstration of remote ischemic perconditioning

Abstract: RK. Intermittent peripheral tissue ischemia during coronary ischemia reduces myocardial infarction through a K ATP-dependent mechanism: first demonstration of remote ischemic perconditioning. Am J Physiol Heart Circ Physiol 292: H1883-H1890, 2007. First published December 15, 2006; doi:10.1152/ajpheart.00617.2006.-Remote ischemic preconditioning reduces myocardial infarction (MI) in animal models. We tested the hypothesis that the systemic protection thus induced is effective when ischemic preconditioning is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
197
1
10

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(209 citation statements)
references
References 31 publications
1
197
1
10
Order By: Relevance
“…Schmidt et al reported the per-ischemic remote technique (rPerC) 9 , which consists in applying remote ischemia through a tourniquet applied to the hind limb of pigs during the main duration of ischemia, which was actually effective in preventing reperfusion injury in ischemia myocardial. This protective effect was corroborated by further studies involving myocardial ischemia, and the procedure was expanded to cerebral ischemia 10,11 .…”
mentioning
confidence: 99%
“…Schmidt et al reported the per-ischemic remote technique (rPerC) 9 , which consists in applying remote ischemia through a tourniquet applied to the hind limb of pigs during the main duration of ischemia, which was actually effective in preventing reperfusion injury in ischemia myocardial. This protective effect was corroborated by further studies involving myocardial ischemia, and the procedure was expanded to cerebral ischemia 10,11 .…”
mentioning
confidence: 99%
“…Perconditioning is the newest technique described to mitigate IR injury in many tissues 15,18,20 . Our study is the first evaluate of the potential protective effect of PER alone or combined with POS on kidney IR-induced injury, that only be test before in myocardium 15,20 , brain 17,26 , and liver 18 .…”
Section: ■ Discussionmentioning
confidence: 99%
“…Based on fact that perconditioning is performed in a distant tissue, is a non-invasive procedure and do not increase the surgical time, thus does not require direct access to the artery and could be easily applied during the surgery or endovascular surgery [15][16][17][18][19] ; this ischemic conditioning must be test in human IR syndromes 20,31 . However, new studies aim to understanding the mechanism are need 32 .…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations